Kontribusi Teori Etika Al-Ghazali untuk Pendidikan Orang Dewasa - Abdul Karim (EL-TARBAWI, 2020)
Akhlak (morality) is one of the three basic frameworks of islamic teachings (akidah, syari'ah and akhlak) which have important position. Moral expression is concrete evidence of the application and embodiment of aqidah and syari'ah, thus, represents the quality of Muslim’s faith. This research is a qualitative research conducted with literature study. This study seeks to explain the ethical concept of al-Ghazali and its application in the world of adult education, as explained by al-Ghazali in his works. The author limited the writings of al-Ghazali which are used as the basis for this research study, only to works written in the last years of his life, especially when he lived life as a Sufi. This research found that al-Ghazali divided adult education methods into two, general and specific. The general method applies to everyone and the specific method applies specifically to everyone based on the results of self-introspection.